miRNA-132-5p mediates a negative feedback regulation of IL-8 secretion through S100A8/A9 downregulation in neutrophil-like HL-60 cells - Zhou, Yang; Nomigni, Milène Tetsi; Gaigneaux, Anthoula; Tolle, Fabrice; Wright, Helen L.; Bueb, Jean-Luc; Bréchard, Sabrina (Frontiers in Immunology, 2024)
Background: Neutrophils are an important source of pro-inflammatory and immunomodulatory cytokines. This makes neutrophils efficient drivers of interactions with immune and non-immune cells to maintain homeostasis and modulate the inflammatory process by notably regulating the release of cytokines. Ca 2+ -dependent regulatory mechanism encompassing cytokine secretion by neutrophils are not still identified. In this context, we propose to define new insights on the role of Ca 2+ -binding proteins S100A8/A9 and on the regulatory role of miRNA-132-5p, which was identified as a regulator of S100A8/A9 expression, on IL-8 secretion. Methods: Differentiated HL-60 cells, a human promyelocytic leukemia cell line that can be induced to differentiate into neutrophil-like cells, were used as a model of human neutrophils and treated with Nformyl-methionyl-leucyl-phenylalanine (fMLF), a bacterial peptide that activates neutrophils. shRNA knockdown was used to define the role of selected targets (S100A8/A9 and miRNA-132-5p) on IL-8 secretion.Results and Discussion: Different types of cytokines engage different signaling pathways in the secretion process. IL-8 release is tightly regulated by Ca 2+ binding proteins S100A8/A9. miRNA-132-5p is up-regulated over time upon fMLF stimulation and decreases S100A8/A9 expression and IL-8 secretion. Conclusion: These findings reveal a novel regulatory loop involving S100A8/A9 and miRNA-132-5p that modulates IL-8 secretion by neutrophils in inflammatory conditions. This loop could be a potential target for therapeutic intervention in inflammatory diseases.